REFORMING UNIVERSITY ACCREDITATION SYSTEMS: POST-COVID-19 CHALLENGES AND PROSPECTS IN NIGERIA, EGYPT, AND MALAWI - Salawu, Rafiu Oyesola; Salawu, Mary Kehinde (African Journal of Social and Behavioural Sciences, 2025)
Credible and quality accreditation across higher education institutions is no longer a luxury but a must for every institution that desires a high global ranking, competence-based education, global labour market penetration, and public trust. The objective of this study was to investigate the general and particular challenges with the system of university accreditation in Nigeria (West Africa), Egypt (Northern Africa), and Malawi (Southern Africa) after the COVID-19 pandemic. The study employed a qualitative approach with the aid of a documentary survey type. The study, being both descriptive and historical, relied essentially on secondary information sources gathered by the researchers. The data were analysed using a narrative method that leaned more on the interpretivist approach. The results showed some common challenges confronting the university accreditation system in the selected three countries, which are dwindling public resources for institutions, the massification of higher education, and the reviewer’s capacity deficit. It also revealed peculiar challenges such as paper-based accreditation (Nigeria and Malawi), digital accreditation in Egypt, and irregular institutional accreditation in Nigeria. The study revealed the prospects (solutions to challenges) and future direction of accreditation in the three countries. The study recommended that virtual-based accreditation, regular program and institutional accreditation, solving the massification of higher education through technology, eradicating academic and accreditation corruption, and recruiting qualified and well-trained reviewers must be embarked upon by relevant accrediting authorities. The digitalisation of accreditation is not optional in the face of high development in information technology.